2023
DOI: 10.1038/s41598-023-28916-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of wavy trapezoidal porous cavity containing mixture hybrid nanofluid (water/ethylene glycol Go–Al2O3) by response surface method

Abstract: Increasing thermal performance and preventing heat loss are very important in energy conversion systems, especially for new and complex products that exacerbate this need. Therefore, to solve this challenge, a trapezoidal cavity with a wavy top wall containing water/ethylene glycol GO–Al2O3 nanofluid is simulated using Galerkin finite element method. The effects of physical parameters affecting thermal performance and fluid flow, including porosity (ℇ), thermal radiation (Rd), magnetic field angle (α), Rayleig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Later, Akbari et al 22 analytically studied the thermal behavior of a 3D hollow sphere. Thermal behavior of porous fin with various cross sections can be noticed in Hosseinzadeh et al 23 and Alipour et al 24 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Later, Akbari et al 22 analytically studied the thermal behavior of a 3D hollow sphere. Thermal behavior of porous fin with various cross sections can be noticed in Hosseinzadeh et al 23 and Alipour et al 24 …”
Section: Introductionmentioning
confidence: 94%
“…Later, Akbari et al 22 analytically studied the thermal behavior of a 3D hollow sphere. Thermal behavior of porous fin with various cross sections can be noticed in Hosseinzadeh et al 23 and Alipour et al 24 The effect of magnetic field plays a vital role in heat transfer phenomena. In this regard, some studies have shown that it helps in enhancing heat transfer rate in fins.…”
Section: Introductionmentioning
confidence: 98%
“…In order to build models and assess issues, the response surface method (RSM) integrates mathematical and statistical methodologies 4 , 5 . The experimental design plan must determine the level of factors that will provide the best response value 6 8 . In the case of a response that is associated with multiple independent factors or variables.…”
Section: Introductionmentioning
confidence: 99%
“…The primary finding of this research is the novel discovery of the superior performance of cross heating-cooling, in contrast to the conventional methods of heating-cooling from the top or bottom sides. Study these papers for further information [ [44] , [45] , [46] , [47] , [48] , [49] ].…”
Section: Introductionmentioning
confidence: 99%